The trophodynamics of marine top predators: Current knowledge, recent advances and challenges - Young, J.; Hunt, B.; Cook, T.; Llopiz, J.; Hazen, E.; Pethybridge, H.; Ceccarelli, D.; Lorrain, A.; Olson, R.; Allain, V.; Menkes, C.; Patterson, T.; et al. (Pergamon, 2015)
© 2014 Elsevier Ltd.We review present understanding of the spatial and temporal diet variability (trophodynamics) of a range of pelagic marine top predators, at both early and adult life history stages. We begin with a review of methodologies used to advance our understanding of the trophodynamics of marine top predators, particularly in relation to climate change. We then explore how these developments are informing our understanding of the major trophic groups in food webs leading to, and including, marine top predators. We examine through specific examples how the impacts of ocean warming may affect pelagic food web relationships from both top-down and bottom-up perspectives. We examine the potential, in the absence of long-term data sets, of using large-scale spatial studies to examine how potential changes in biological oceanography could impact the biomass and composition of prey species, particularly the role of phytoplankton size spectra. We focus on examples from regions where biotic change with respect to climate change is likely. In particular, we detail the effects of climate change on oceanographic and bathymetric "hotspots" and provide the example involving seabirds in the Benguela Current system. We end by urging the development of international collaborations and databases to facilitate comprehensive ocean-scale understanding of climate impacts on marine top predators.